(untitled) (Hekima Review, 2010)
In a world so divided between religious and non-religious or sacred and secular notions of reality, the title of this little volume on spirituality in sports strikes one as at least somewhat odd, if not outright out of place. How can anyone talk about “spirituality” in reference to such seemingly so “worldly” an activity as sports? When one thinks about spirituality one has usually in mind religious rituals such as prayers, meditation and so on. And when one talks about sports, “religion” in the formal sense of the word is one thing that is normally furthest from the mind.